The training of Nursing academics in the Amazon context: the black and quilombola populations (Research, Society and Development, 2021)
In this article, the objective is to reflect on the training of nursing students from Higher Education Institutions (HEIs) in the western region of Pará with regard to comprehensive health care for black/quilombola populations. It is a descriptive research with a qualitative approach. The study participants were nursing professors and academics from two HEIs in Santarém-PA. Individual interviews were conducted and the IRAMUTEQ software was used to assess the speeches, through the Descending Hierarchical Classification tool, for qualitative and quantitative assessment. It was found that both professors and academics have basic knowledge about the National Policy for Comprehensive Health of the Black Population (PNSIPN) and about the peculiarities of this population's way of life. It was also found that HEIs still have difficulty in putting into practice the proposal of the Pedagogical Course Project (PPC), which is a pedagogical planning and evaluation tool that guides the curricular guidelines of nursing courses.